Gut Microbiota Influence Lipid Metabolism of Skeletal Muscle in Pigs - Wu, Choufei; Lyu, Wentao; Hong, Qihua; Zhang, Xiaojun; Yang, Hua; Xiao, Yingping (Frontiers in Nutrition, 2021)
Gut microbiota is recognized as a strong determinant of host physiology including fat metabolism and can transfer obesity-associated phenotypes from donors to recipients. However, knowledge of relationship between the gut microbiota and intramuscular fat (IMF) is still limited. Obese Jinhua pigs (JP) have better meat quality that is associated with higher IMF content than lean Landrace pigs (LP). The present study was conducted to test the contribution of gut microbiota to IMF properties by transplanting fecal microbiota of adult JP and LP to antibiotics-treated mice. Similar to JP donors, the mice receiving JP’s microbiota (JM) had elevated lipid and triglyceride levels and the lipoprotein lipase activity, as well as reduced mRNA level of angiopoietin-like 4 (ANGPTL4) in the gastrocnemius muscles, compared to those in mice receiving LP’s microbiota (LM). High-throughput 16S rRNA sequencing confirmed that transplantation of JP and LP feces differently reconstructed the gut microbiota in both jejunum and colon of mouse recipients. In colonic samples, we observed an elevated ratio of Firmicutes to Bacteroidetes and increased abundance of genus Romboutsia in JM, which are positively correlated with obesity. Furthermore, the abundance of Akkermansia decreased in JM, which is positively correlated with lean. Colonic concentrations of acetate (P = 0.047) and butyrate (P = 0.014) were significantly lower in JM than in LM, and consistently, the terminal genes for butyrate synthesis, butyryl CoA: acetate CoA transferase were less abundant in colonic microbiome of JM. Taken together, the gut microbiota of obese JP intrinsically promotes IMF accumulation and can transfer the properties to mouse recipients. Manipulation of intestinal microbiota will, therefore, have the potential to improve the meat quality and flavor of pigs and even to ameliorate the metabolic syndrome in human.